The state-of-the-art on Refrigerants. (August 2020) - Cavallini, A
Abstract: The two recent global emergencies (stratospheric ozone depletion and global warming) force refrigerating engineers and operators to face a new revolution on the choice of the working fluids for the different applications of refrigeration technology. Chemistry by now runs short of new synthetic products meeting within acceptable limits all the requirements asked for by the different refrigeration applications, and compromise solutions are more and more necessary, involving a limited use of few old-generation fluids, the new family of products HFO and an increased consideration for natural refrigerants. While dealing with these topics, this paper will show how basic thermodynamics can highlight important characteristics of a refrigerant.